Analisis Peran Modal Sosial oleh Pelaku Usaha Sektor Informal yang Bermitra di Go-Food Yogyakarta - Wulandari, Meisyaroh Catur; Avida, Faricha Karin; Rinanda, Nurzidta Okta; Pramesti, Riza Indah; Wiyono, Vincent Hadi (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2023)
Yogyakarta is an area with great potential for the growth of the informal sector. Because this area has many people who are immigrants. LD FEB UI research states that 95% of businesses in the food and beverage sector are growing and the number of go-food transactions is also growing. The increase in go-food partners is because Gojek has the optimism (trust) to help MSMEs grow. This makes researchers want to look further into the analysis of the role of social capital by actors who run food and beverage businesses partnering with Go-Food in Yogyakarta. The object of research is informal sector business actors who sell heavy food in the Province of D.I. Yogyakarta with a focus on the area of Sleman Regency and Yogyakarta City. Researchers used descriptive qualitative methods, with the theory of Miles and Huberman. The results of the study show that the analysis on social capital aspects seen from trust, norms, and networks makes a positive contribution to increasing sales of informal sector actors in Yogyakarta